EVALUATIONG THE PERFORMANCE OF SENIOR MANAGEMENT FOR THE EXTENSION ORGANIZATION IN LIGHT OF THE TOTAL QUALITY STANDARDS FROM THE STANDPOINT OF AGRICULTURAL EXTENSION WORKERS IN GOVERNORATES OF BAGHDAD AND DIYALA FROM IRAQ - & Naji, Hussain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This was aimed to identify the performance of the senior management of the extension organization in light of the comprehensive quality standards from the point of view of agricultural extension workers in the governorates of Baghdad and Diyala in Iraq through the following:Identify the field of planning, identify the field of decision-making, identify the field of humam relations.Data from agricultural extension workers in the governorates of Baghdad and Diyala, which included a graded pentagonal scale consisting of degrees of approval with grades ranging between 5-1 To measure the degree of application of comprehensive quality standards for higher management in the fields from the viewpoint of the agricultural extension workers in the above-mentioned governorates.The governorates of Baghdad and Diyala were selected as an area for conducting the research, as the research community included 38 agricultural divisions, at a rate of20%and by8divisions,and a random sample of510 agricultural extension workers was withdrawn, amounting to20%and by102 agricultural guides.The results showed that the weighted mean for the field of planning from the viewpoint of agricultural extension agents was 3.189,which is close to a certain extent from the hypothetical mean of 3 and a percentage weight 63.78%.With regard to the field of human relations,it came with a weighted mean3.136.